Virtual robotics in education: The experience of eighth grade students in STEM - Alsoliman, Badr Salman H. (Frontiers in Education, 2022)
Classroom teaching with robotics points to a more engaging learning environment in many respects, particularly in terms of tasks related to problem solving and critical thinking in education. Nevertheless, previous studies have cited many obstacles to using robotics in the classroom. These obstacles include the costs of supplying students with robots, fixing and modifying the robots, and school facilities and infrastructure that negatively influence a teacher’s ability to teach a particular STEM subject or to apply new teaching approaches with robotics; these issues seem to have discouraged some teachers from utilizing robotics in their teaching approaches. Accordingly, this study aims to facilitate teaching with robotics through the use of virtual robotics. The study explores the experience of eighth grade students and their teachers engaging with a virtual platform in five different K–12 schools that have formally incorporated physical robotics into STEM classroom teaching. A qualitative phenomenological approach is utilized to explore the experience, using focus groups with students and interviews with teachers. The focus of this study is on the processes of teaching and learning STEM with robotics via virtual platforms, and the perceived effectiveness and practicability of the virtual platform. The study revealed that the use of virtual classrooms and applications has become acceptable by many educational institutions, influenced to move to online platforms during the COVID-19 pandemic. This has laid the foundation for teachers and students, as the end users and main actors in education, to invest the time and effort in improving STEM and other related skills using virtual robotics. They were motivated by the perceived and acquired benefits that are associated with using virtual robotics in a web-mediated educational process. The main barriers were associated with web-mediated cultural norms and educational regulations/policies related to virtual learning. The main recommendations of the study are for teachers to be innovative, to observe, and to listen carefully to their students, relying on their pedagogical knowledge to use available technology to serve student-teacher objectives.